(untitled) (Jurnal Geomine, 2015)
PT. Anugerah Harisma Barakah is a national mining company who is engaged in mining nickel in the area South Kabaena, Southeast Sulawesi Province which began a nickel ore exploration in 2007. Purpose of this study was to create a model of lateritic nickel deposits in the form of 2 dimensional and 3 dimentional. Datneeded for modeling 2 dimensional and 3 dimensional pont data includes drill block C. Data taken in the form of drilling data in the form of cast data, amounting to 91 points, drills, and the data point coordinates of each drill hole is at the study site in addition to the map block II drill point spread is also very necessary. From this research found Ore depths ranging from 3 to 14 meters with grading 1.5 % - 2.0 % and the number of resources 1,553,325 tons .